1995
DOI: 10.1038/ki.1995.24
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous calcitriol normalizes insulin sensitivity in uremic patients

Abstract: Recent studies suggest that secondary hyperparathyroidism and/or vitamin D deficiency are responsible for the insulin resistance in chronic renal failure. We investigated the effect of a 12-week intravenous treatment with 1,25 dihydroxycholecalciferol on glucose metabolism in 10 hemodialysis patients compared with 10 healthy control subjects by the frequently-sampled intravenous glucose tolerance test, analyzed with the minimal model technique. Compared to control subjects, the uremic patients featured elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 36 publications
2
70
1
2
Order By: Relevance
“…Insulin resistance is a common feature of ESRD, and an independent predictor of cardiovascular death in hemodialysis patients [32]. However, treatment with 1,25 dihydroxyvitamin D significantly improves insulin sensitivity in severely insulin resistant hemodialysis patients [33] and has been shown to be independently associated with reduced risks for cardiovascular [34] and all-cause death [35] in the hemodialysis population. Taken together, these studies suggest that vitamin D may have multiple effects in skeletal muscle, regulating processes that contribute to muscle anabolism, metabolism, and function, with far reaching effects on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is a common feature of ESRD, and an independent predictor of cardiovascular death in hemodialysis patients [32]. However, treatment with 1,25 dihydroxyvitamin D significantly improves insulin sensitivity in severely insulin resistant hemodialysis patients [33] and has been shown to be independently associated with reduced risks for cardiovascular [34] and all-cause death [35] in the hemodialysis population. Taken together, these studies suggest that vitamin D may have multiple effects in skeletal muscle, regulating processes that contribute to muscle anabolism, metabolism, and function, with far reaching effects on survival.…”
Section: Discussionmentioning
confidence: 99%
“…16 Intravenous 12-week vitamin D treatment of HD patients led to a significant reduction of PTH levels and to a complete normalization of insulin sensitivity. 6 Since there was a signi¢cant reduction of PTH levels upon treatment, the authors could not di¡erentiate between the actions of calcitriol per se and those of PTH reduction. The effect of four-week intravenous calcitriol therapy on insulin metabolism was therefore examined, during which time the PTH concentration did not change, so that the direct actions of calcitriol could be assessed independently.…”
Section: Discussionmentioning
confidence: 99%
“…7 Intravenous vitamin D treatment leads to a signi¢cant reduction of PTH concentrations and to a complete normalization of insulin sensitivity in HD patients. 6 Thus, intravenous 1,25 dihydroxycholecalciferol improves insulin resistance in uraemic patients, acting per se or by reducing secondary hyperparathyroidism. In our study, treatment with pulse oral 1-a-D3 only had an e¡ect on PC-1 of Con A-transformed lymphocytes of haemodialysed patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an increased insulin release causing hypoglycemia following parathyroidectomy was observed in a hemodialysis patient (24). The majority of authors, however, observed hyperinsulinemia or insulin resistance in PHPT (15)(16)(17), in secondary hyperparathyroidism (15,25,26) or in hyperparathyroidism associated with multiple endocrine neoplasia syndrome type 1 (18). It is believed that hyperinsulinism and insulin resistance play a role in the pathogenesis of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%